2013
DOI: 10.5897/ajar2013.7028
|View full text |Cite
|
Sign up to set email alerts
|

Sources and rates of nitrogen in the cultivation of flax

Abstract: This study aimed to evaluate the potential development of golden flaxseed (Linum usitatissimum L.) under the influence of the application of sources and rates of nitrogen. The experiment was conducted in the field Unioeste, Campus Cascavel, State of Paraná, using the factorial design (2×5) randomized, two nitrogen sources (urea and ammonium sulphate) and five rates of nitrogen (0, 50 , 100, 150 and 200 kg ha-1). We evaluated the following characteristics: plant height, fresh (FWP) and dry weight (DWP) of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…and straw yield per plant, hence straw yield per feddan was highest. These results are in harmony with those of El-Gazzar andKineber (2002),El-Nagdy et al (2010),Geovan et al (2013),Dervisevic et al (2014) andEl-Borhamy (2016). Data recorded in Tables 3-13 show clearly that flax varieties were significantly differed in both 2016/2017 and 2017/6018seasons .…”
supporting
confidence: 89%
See 1 more Smart Citation
“…and straw yield per plant, hence straw yield per feddan was highest. These results are in harmony with those of El-Gazzar andKineber (2002),El-Nagdy et al (2010),Geovan et al (2013),Dervisevic et al (2014) andEl-Borhamy (2016). Data recorded in Tables 3-13 show clearly that flax varieties were significantly differed in both 2016/2017 and 2017/6018seasons .…”
supporting
confidence: 89%
“…El-Nagdy et al (2010) reported that 45 kg N/fed have highest seed and straw yields. Geovan et al (2013) reported that nitrogen rates influenced some production components. Dervisevic et al (2014) reported that the optimal nitrogen rate for fiber flax to the obtained results was 30 kg N/ha.…”
Section: Introductionmentioning
confidence: 99%
“…These findings align with [30], suggesting that linseed, is characterized by great phenotypic plasticity with a considerable adaptability to changes in spacing. The increased stem branching in our fiber flax cultivation agrees with [26], who noted that higher nitrogen soil concentrations were associated with an increased number of stem branches in golden flaxseed. Additionally, flax varieties considered for fiber production typically exhibit less branching, featuring thinner straw and lacking sub-stems [7].…”
Section: Discussionsupporting
confidence: 91%
“…Previous researches underline the complex interaction of factors that impact flax development, such as residual soil nitrogen, soil type, flax cultivar, climate and moisture conditions, and growing cycle duration [10,14,[22][23][24][25][26]. Furthermore, the key roles of plant density, climatic conditions, and nitrogen levels in shaping stem branching in flaxseed have been emphasized in various studies [25][26][27][28][29][30]. Understanding the importance of these factors is crucial when evaluating flax branching patterns, as they significantly affect plant architecture and yield.…”
Section: Discussionmentioning
confidence: 99%
“…The augmentation of the biomass (DM) of the plants due to the application of N fertilization has also been reported by other researchers. Soethe et al [39] noted a positive linear increase while examining the interaction of N fertilization and the biomass of flax plants. In our study, during both experimental years, the dry weight of the plants was significantly affected by fertilization, particularly on treatments with higher fertilization rates (Figure 1).…”
Section: Discussionmentioning
confidence: 99%